(untitled) (Research, Society and Development, 2020)
Permanent Health Education (EPS) is based on the assumption of meaningful learning, by bringing the world of work closer to the world of education, where the learning environment is the very space of health services. Objective: The present study reports the experience of an interventionist action through the construction of an assistance protocol based on the assumptions of EPS mediated by conversation wheels, in a highly complex university hospital service in the state of Rio Grande do Sul. Results: During the interventions, the conversation wheels allowed horizontal conversation. The assistance protocol was produced collectively, alliances were made, discoveries of the weaknesses and potential of the service, we managed to create some ways in a collective way to facilitate assistance. Conclusion: We understand that EPS and its proposal for conversation circles allows the elaboration of many work actions, processes, flows and protocols and mainly, it allows us to discuss scientific evidence in an informal and collective way.